OECD uses IMPACT model for climate-smart agriculture strategies - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
The Organisation for Economic Co-operation and Development (OECD) has a mission to promote policies that improve economic and social well-being around the world. In 2014 the OECD used a model developed by the International Food Policy Research Institute (IFPRI) as part of a project supported by CCAFS to create sophisticated projections of agricultural commodities and trade.